(untitled) (Conferencea, 2024)
It is very important to identify the climate changes currently observed all over the world. To do this, it is important to know what is the climate that was initially happening in the Republic of Uzbekistan and now. Knowing this, we are greatly helped by the air temperature and the annual fat content. If we can evaluate what the current climate is like, scientifically, mathematically, statistically, it can help us a lot in terms of climate changes that occur in the coming years and forecasting them.